Manage Employee Work Stress with Group Counseling Intervention - Rahma Ardiani; Rizqi Zulfa Qatrunnada (Prosiding University Research Colloquium, 2021)
This research aims to determine the group counseling intervention to manage work stressof PT D's production executives during the application of work from office policies duringpandemic. This study uses a quantitative method with a questionnaire instrument. Thescale used is 14 items measuring the CD-RISC resilience variable and 9 items measuringthe DASS work stress variable. The sampling technique used is purposive sampling.Respondents amounted to 45 people. The data analysis technique used Pearson ProductMoment correlation. The results showed that there was an insignificant relationshipbetween resilience and work stress of PT D production executives. It can be concluded thatresilience is not the main factor in dealing with work stress. Researchers giverecommenation intervention held a group counseling to decrease work stress impact.